Robots swarm communication control based on biological behavior inspiration - Mushreq Abdulhussain Shuriji; Hussein A. Abdulnabi; Tariq Mohammed Salman (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Robot swarming, increasingly find importance in the last decade. In these systems, multi mobile robots have to work cooperatively to perform specified tasks. One of the compelling problems is that the robots movements should be in such a way that they should follow a specific guide and at the same time they should have the ability of obstacle avoidance. Inspiriting such movement from biological swarms is a compelling problem. Fish schools, bird flocks and sheep herds are particular examples of biological systems swarming. In this paper, a robot swarming algorithm was developed based on swarming rules noticed in these biological systems, the combination between the swarm members and the leadership control also explained, an ad-hoc non-essential communication system was proposed for the purpose of use in case of collective takeoff and collective landing swarm-robots, in which activated automatically.